A Novel High-Throughput Sample-in-Result-Out Device for the Rapid Detection of Viral Nucleic Acids - Fangning Wang; Fei Hu; Yunyun Zhang; Xichen Li; Qin Ma; Xincheng Wang; Niancai Peng (Biosensors)
Clustered regularly interspaced short palindromic repeats (CRISPR) molecular diagnostic technology is one of the most reliable diagnostic tools for infectious diseases due to its short reaction time, high sensitivity, and excellent specificity. However, compared with fluorescent polymerase chain reaction (PCR) technology, CRISPR molecular diagnostic technology lacks high-throughput automated instrumentation and standardized detection reagents for high sensitivity, limiting its large-scale clinical application. In this study, a high-throughput automated device was developed by combining reagent lyophilization, extraction-free technology, and a one-pot consumable system. This innovative approach enabled the rapid sample-in-result-out detection of 48 samples in 25 min and demonstrated high sensitivity and specificity for the qualitative analysis of clinical samples. The obtained results show that the detection limit of the designed system for African swine fever virus (ASFV) is 0.5 copies/μL. As a proof concept, a single-tube dual-target nucleic acid detection method was developed, achieving a detection limit of 5 copies/μL for the ORF1ab and N genes of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) within 45 min. The method is highly specific, reliable, and stable, providing a feasible solution for the clinical application of CRISPR nucleic acid detection technology.